Historical documentation of the ancient mosque “Sheikh Daoudi” in the Ouled Mimoun area – Tlemcen - Dahmani, Omar Jamal Al-Din (The Algerian Historical Journal, 2026)
The Oulad Mimoun region was blessed with the establishment of the first mosque during the French colonial era. It is an ancient mosque whose construction was intended to be a beacon of knowledge and a base for consolidating national identity and strengthening the components and foundations of the region’s population in the face of all methods of colonial administration, which sought to obliterate everything connected to the identity of the Algerian people. It is a historical landmark that the Ould Mimoun region enjoyed, to remain a witness to a bright period of time in the glorious history of the region. This landmark was established due to the desire of men loyal to their homeland who were the first to think about establishing a mosque in the region, as well as the residents of the region who formed the most appropriate and ideal embrace to contain it. The mosque.